Enhancing Financial Management in Secondary Schools through a Participatory Intervention - Njini, Stephen; Elda, Hungwe (LPPM Universitas Jambi, 2026)
This study aims to address financial management challenges in secondary schools by adopting a social work–oriented, participatory intervention approach. Previous studies have primarily focused on identifying governance issues such as weak accountability, limited financial literacy, and inadequate policy adherence, with limited emphasis on practical, stakeholder-driven solutions. This study employed a Participatory Action Research (PAR) design consisting of three phases: needs assessment, intervention, and evaluation. Data were collected through questionnaires, interviews, and document analysis involving school heads, teachers, School Development Committee (SDC) members, and education officials. The findings from the baseline assessment revealed significant gaps in financial governance, including poor record-keeping, lack of training, and weak institutional structures. Following the implementation of a capacity-building intervention—comprising workshops, mentoring, and participatory discussions—participants demonstrated improved financial management knowledge, enhanced governance practices, and increased stakeholder engagement. The novelty of this study lies in integrating social work principles, particularly empowerment and participation, into educational financial governance. The study implies that sustainable improvements require not only technical training but also inclusive, context-sensitive interventions that strengthen both individual capacity and institutional systems.